Lunar Solar Occultation Explorer (LunaSOX) - Cooper, John F.; Habbal, Shadia R.; Boe, Benjamin; Angelopoulos, Vassilis; Sibeck, David G.; Paschalidis, Nikolaos; Sittler, Edward C.; Jian, Lan K.; Killen, Rosemary M. (Frontiers in Astronomy and Space Sciences, 2023)
In the present decade and beyond, now fifty-one years after the last Apollo landing, the NASA Artemis human exploration program will offer abundant opportunities for heliophysics investigations from, by, and of the Moon from the vantage points of lunar orbit and the surface. The Lunar Solar Occultation Explorer (LunaSOX) concept uses the lunar limb to occult the solar disk for high-resolution coronal observations at hourly, daily, to biweekly cadence from spacecraft either in lunar orbit or at the surface. A 0.2-m diameter solar telescope in orbit with white light and narrow-band visible filters would provide arcsecond spectroscopic imaging of the low to high corona (1 – 10 R☉) with an upper limit of 10^-12 B☉ on local scattered light background from lunar atmospheric dust, as compared to 10^-9 B☉ for Earth ground-based solar eclipse observations looking up through the atmosphere at totality. For eclipse observations from and by the Moon there would be no significant atmospheric disturbances that otherwise limit seeing to arcsec resolution from the Earth's surface. The present eccentric orbits of the ARTEMIS P1 and P2 spacecraft are used as models for a 1x10 Rm orbit of LunaSOX to compute times of solar eclipse intervals, up to two hours in duration between east and west solar hemispheres at daily cadence for coronal observations at 1 – 16 R☉ when the orbital aposelene is in anti-sunward directions. In low altitude circular orbit and from the surface the observational cadences would, respectively, be hourly and biweekly. LunaSOX satellites also carrying in-situ space environment instruments could integrate into a network of orbital platforms for space weather monitoring and communications relay to farside surface lander and permanent base sites, e.g. for low-frequency radio cosmology and detection of exoplanet magnetospheres.